Prevalence and risk factors associated with depression in pregnant adolescents in Nairobi, Kenya - Albert Tele; Joseph Kathono; Shillah Mwaniga; Vincent Nyongesa; Obadia Yator; Onesmus Gachuno; Dalton Wamalwa; Beatrice Amugune; Pim Cuijpers; Shekhar Saxena; Mary McKay; Liliana Carvajal; et al. (Journal of Affective Disorders Reports, 2022)
Background: Adolescent parenthood can be associated with a range of adverse outcomes for young mothers such as depression, substance abuse, and posttraumatic stress disorder. Identification of depression and understanding risk factors among pregnant adolescents is important for development of appropriate interventions and programs focused on adolescent mental health. This paper reports on the findings of the prevalence of depression and its associated risk factors among pregnant adolescents in Nairobi, Kenya. Methods: We recruited 153 pregnant adolescent (14-18 years) who were accessing maternal health services in one of two Nairobi County primary health care facilities in the cross-sectional survey conducted in 2021. The Patient Health Questionnaire 9 was used to screen for depression. Multivariate Stepwise linear regression modelling was used to identify key predictors of depression. Results: Using a cut off of 10 and above on PHQ-9, we found that 43.1% of the respondents were depressed. Depressive symptoms in were independently associated with being in school, experience of intimate partner violence, substance use within the family and having experienced pressure to use substances by family or peers. Limitations: Cross-sectional by design and the applications of our findings are limited to settings that are similar to our study population. The PHQ-9 used has not been psychometrically validated locally in this sample. Conclusion: We found a high prevalence of depressive symptoms among respondents. These risk factors identified merit further investigation. Comprehensive mental health screening needs to be integrated in primary and community health services on the possible presence of depression.